The collaborative innovation bloc: A new mission for Austrian economics - Niklas Elert; Magnus Henrekson (Research Institute of Industrial Economics (IFN), 2018)
We argue that scholars in the Austrian tradition of economics should incorporate the notion of a collaborative innovation bloc into their study of spontaneous market order. We demonstrate how successful entrepreneurship depends on an innovation bloc of this kind, a system of innovation that evolves and within which activity takes place through time. The innovation bloc consists of five pools of economic skills from which people are drawn or recruited to form part of a collaborative team, which is necessary if innovation-based venturing is to flourish. The five skills are entrepreneurs, early- and later-stage-financiers, key personnel, and customers. Through real-world examples, we show how the application of the collaborative innovation bloc perspective could help make Austrian economics more concrete, relevant and persuasive, especially in regard to policy prescriptions.​
Keywords: B53; D20; G32; L23; L26; O33; 330; Austrian Economics; Entrepreneurship; Innovation; Institutions; Schumpeterian entrepreneurship; Spontaneous order